A good bake : the art and science of making perfect pastries, cakes, cookies, pies, and breads at home - Weller, Melissa; Carreño, Carrolynn (Alfred A. Knopf, 2020)
"A comprehensive baking bible for the twenty-first century from the James Beard nominee who has redefined American baking. With 120 scientifically grounded recipes for sweet and savory baked goods anyone can master"--